The Effect of Workload on Burnout Among Employees at The Balcone Suites and Resort Bukittinggi - Anjelita, Vanessa; Rahmi Fadilah (Pt. Threeple Herphi Educate, 2025)
This study investigates the effect of workload on employee burnout in the hospitality industry, using The Balcone Suites and Resort Bukittinggi as a case study. The research is motivated by the high operational intensity in hotels, which may contribute to physical, emotional, and mental exhaustion among employees. A quantitative causal-associative approach was applied, involving a total sampling of 88 permanent employees. Data were collected using a structured Likert-scale questionnaire and analyzed through simple linear regression with SPSS version 25.0, following normality, homogeneity, and linearity assumption tests. The results reveal that workload has a significant positive effect on burnout (p < 0.05), with an Adjusted R2 value of 0.340, indicating that workload explains 34% of the variance in burnout. These findings suggest that as workload increases, burnout levels also rise, underscoring the importance of workload management in reducing employee fatigue and sustaining service quality. This study contributes to the limited empirical literature on workload–burnout relationships in the hotel sector, offering practical implications for managers to implement balanced task allocation, flexible scheduling, and stress management training